The effect of exercise intensity on sweat rate and sweat sodium loss in well trained athletes - Holmes, N.; Miller, V.; Bates, G.; Zheo, Y. (Journal of Science and Medicine in Sport, 2011)
Introduction: Endurance athletes often train and compete in harsh environmental conditions prompting high sweat losses. The need to replace fluid lost during exercise is well documented however the replacement of sweat sodium losses has had far less focus. Symptoms of sodium depletion include fatigue, muscular weakness, muscle cramps and in severe cases may lead to circulatory failure. This study was designed to better understand the sweat rate and sweat sodium losses that occur during exercise of varying intensities in order to be able to more accurately determine sodium intake requirements in athletes. Methodology: Eighteen male endurance athletes (age 38.6 ± 9.9 years, Weight 83.2 ± 13.6 kg, VO2max 57.4 ± 9.7 ml/kg.min) volunteered to be part of the study. Subjects were randomised into one of three groups for the experimental trials. Group 1(L) began with the low intensity trial (40%VO2max), group 2 (M) with the moderate intensity trial (70%VO2max) and group 3 (H) with the high intensity trial (time trial). All subjects performed each of the three trials one week apart. Each trial consisted of 15 mins warm up followed by 15 mins at the various intensities where sweat was collected from the arms and legs. Results: There was a significant (p<0.05) increase in sweat rate with increasing exercise intensity in all 18 subjects (L= 1.0L/hr ± 0.3, M = 1.5L/hr ± 0.4, H = 1.9L/hr ± 0.3). There was also a significant increase (p<0.05) in sweat sodium concentration between the Low and the High exercise trials (L = 30.0mmol/L ± 2.5, H = 49.4mmol/L ± 5.3). Estimated average sodium loss (mg/hr) based on an individual`s sweat rate ranged from 700mg/hr in the low intensity trial to 1350mg/hr in the moderate trial and 2200mg/hr in the high intensity trial. Conclusion: There is considerable individual variation in sweat rate and sodium loss in athletes. This further highlights the need for fluid and sodium recommendations to be specific to the individual athlete based on their sweat rate, the environmental conditions as well as the type, intensity and duration of exercise. Based on these results the predicted sweat sodium loss in a high salt sweater training 4 hours per day could potentially be as high as 7-10g sodium (Na) or 17.5 - 25g salt (NaCl). Emphasis on the replacement of both fluid and electrolyte losses accompanying prolonged exercise in the heat is important in order to avert potential heat related illness and maintain performance.